Climate literacy, sustainability and culturally responsive language teaching: Reimagining teacher education in Fiji - Tulomana, Josaia; Tagimaucia, Varanisese; Nayasi, Kasanita (Issues in educational research, 2025)
This study examines the integration of climate literacy and cultural responsiveness within i-Taukei and English language courses for pre-service teachers and language educators at a teacher training college in Fiji. Grounded in constructivist learning theory, our research identifies key barriers, including limited resources, time constraints, and the urgent need for culturally relevant pedagogical approaches. The findings underscore the necessity for embedding climate literacy within language curricula, enhancing professional development focused on cultural responsiveness, and fostering collaborations with local communities to attain sustainable educational practices. These insights advocate for curriculum reforms promoting sustainable development within language education in teacher training programs.